Gum Arabic (Acacia Senegal) Augmented Total Antioxidant Capacity and Reduced C-Reactive Protein among Haemodialysis Patients in Phase II Trial. (9th April 2020) - Ali, Nour Elkhair; Kaddam, Lamis AbdelGadir; Alkarib, Suad Yousif; Kaballo, Babikir Gabir; Khalid, Sami Ahmed; Higawee, Abdalazim; AbdElhabib, Alaa; AlaaAldeen, Alaa; Phillips, Aled O.; Saeed, Amal Mahmoud
Abstract : Background . Oxidative processes might increase in patients with end-stage renal disease (ESRD) according to the current literature. Oxidative stress (OS) is a risk factor of atherosclerosis and cardiovascular complications, which are major causes of mortality among ESRD patients. Haemodialysis (HD) is life-saving procedure, nevertheless it is an active chronic inflammatory status that could augment cardiovascular disease and increase mortality. Gum Arabic (GA) has been claimed to act as an antioxidant and anti-inflammatory agent in experimental studies and clinical trials. Therefore, we assumed GA supplementation among haemodialysis patients would reduce oxidative stress and consequently reduce the state of chronic inflammatory activation associated with haemodialysis. Methods . Forty end-stage renal failure (ESRF) patients aged 18–80 years who were on regular haemodialysis in Arif Renal Center, Omdurman, Sudan, were recruited. All recruited patients met the inclusion criteria and signed informed consent prior to enrolment. The patients received 30 g/day of GA for 12 weeks. C-reactive protein (CRP) and complete blood count (CBC) were measured as baseline and monthly. Total antioxidant capacity (TAC) and oxidative stress marker malondialdehyde (MDA) levels were measured before and after GA intake. Ethical approval from the National Medicines and Poisons Board was obtained. Results . Gum Arabic significantly augmented total antioxidant capacity level (P < 0.001 ) (95% CI, 0.408–0.625) and also attenuated oxidative marker MDA and C-reactive protein (P < 0.001 ). Conclusions . GA has revealed potent antioxidative and anti-inflammatory properties in haemodialysis patients. Oral digestion of GA (30 g/day) decreased oxidative stress and inflammatory markers among haemodialysis patients. Trial registration. ClinicalTrials.gov Identifier: NCT03214692, registered 11 July 2017 (prospective registration).